CHARACTERISTICS OF COMBUSTION AND PHYSICAL PROPERTIES OF COFFEE GROUNDS AND SAGO PULP BRICKS WITH SAGO FLOUR BINDER - Haurissa, Calvion Jean; Joni, Joni; Ranteallo, Obet Takke; Numberi, Johni J; Palamba, Phiter; Karapa, Enos; Haurissa, Jusuf (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
This study examines the production of briquettes based on agricultural waste from sago pulp and coffee grounds using natural sago flour as a binder, through a laboratory experimental approach. The analysis covers the physical and chemical characteristics, as well as the thermal performance of 3 cm cube-shaped briquettes. The results show that coffee pulp briquettes have the highest heat transfer rate (0.528 Watts) and the highest calorific value (5018 kcal/kg), indicating superior combustion efficiency compared to sago pulp briquettes (0.205 Watts; 4856 kcal/kg) and mixed briquettes (0.347 Watts; 4966 kcal/kg). These differences in characteristics were influenced by the composition of the materials, while the size of the briquettes affected the ignition time. Overall, all types of briquettes showed potential as an environmentally friendly alternative energy source based on local biomass.